2007
DOI: 10.1016/j.jtcvs.2006.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Intramural hematoma and thoracic aortic aneurysm with syphilis

Abstract: yphilitic aortitis is usually associated with aortic aneurysm, aortic regurgitation, and coronary ostial stenosis. 1 However, aortic dissection and intramural hematoma (IMH) due to syphilitic aortitis have rarely been reported. We present a case of ascending aortic IMH and aortic arch aneurysm with syphilis; the patient underwent total arch replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Intramural hematoma of the ascending aorta has also been described recently in this context. 1 The pathological hallmark is endarteritis obliterans of the vasa vasorum with a chronic inflammatory infiltrate, ischemic necrosis, and fibrosis of the medial layer. Scarring of the aortic media leads to longitudinal wrinkling of the aortic wall (tree barking); however, extension of the disease into the aortic root with coronary ostial stenosis appears to occur in a minority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Intramural hematoma of the ascending aorta has also been described recently in this context. 1 The pathological hallmark is endarteritis obliterans of the vasa vasorum with a chronic inflammatory infiltrate, ischemic necrosis, and fibrosis of the medial layer. Scarring of the aortic media leads to longitudinal wrinkling of the aortic wall (tree barking); however, extension of the disease into the aortic root with coronary ostial stenosis appears to occur in a minority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Autopsies of patients with syphilitic aortitis have shown that findings in 9% of cases are isolated to the descending aorta 20 . Other articles have documented eccentric thickening of the aorta in addition to findings such as intramural hematoma and dissection 19,31 …”
Section: Resident Discussionmentioning
confidence: 99%
“…[1,4] Neurosyphilis was common befor the penicillin era, but now it is uncommon as effective treatment is available. [1] Several case reports have described association between syphilis and aneurysms, [5] infarction, [6] or both conditions. [7] In Taiwanese patients, atherosclerosis is the common cause of carotid occlusion, of the forty-four patients studied, only one patients had arterial occlusion due to syphilis.…”
Section: Discussionmentioning
confidence: 99%